A Strategic Planning For A CollegeStudent-Segment Shopping Mall - Astri Anindya Sari; Hanson Endra Kusuma; Baskoro Tedjo (Universitas Prasetiya Mulya, 2011)
In the midst of shopping mall development today, an understanding of consumer behaviors and preferences is absolutely a must if we want to plan successfuly a shopping mall. This knowledge will provide input for strategic planning so that the concept offered for shopping mall development will meet the consumers’ demand and may win the market competition. This study explores the preferences of students in Bandung as one of the potential market segments of the shopping mall. Qualitative study was conducted to find out the reasons why students choose a particular shopping mall as their favorite place. It was found that the accessibility and design of the malls are important as they enhance student preferences. In addition facilities in a shopping mall which mainly attract college students segment are entertainment facilities and eating counters.